2021
DOI: 10.3389/fnut.2021.765147
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Key Genes for Milk Fat Synthesis in Ruminants

Abstract: Milk fat is the most important and energy-rich substance in milk and plays an important role in the metabolism of nutrients during human growth and development. It is mainly used in the production of butter and yogurt. Milk fat not only affects the flavor and nutritional value of milk, but also is the main target trait of ruminant breeding. There are many key genes involve in ruminant milk fat synthesis, including ACSS2, FASN, ACACA, CD36, ACSL, SLC27A, FABP3, SCD, GPAM, AGPAT, LPIN, DGAT1, PLIN2, XDH, and BTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 126 publications
(204 reference statements)
0
28
0
Order By: Relevance
“…The increased intramuscular fat accumulation in goats fed ABSF is most likely due to the increased rumen acetate production. In fact, an increase in acetate production makes more substrate accessible for de novo fat synthesis ( 41 ). Previous research found a negative relationship between intramuscular fat content and WBSF tenderness values ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased intramuscular fat accumulation in goats fed ABSF is most likely due to the increased rumen acetate production. In fact, an increase in acetate production makes more substrate accessible for de novo fat synthesis ( 41 ). Previous research found a negative relationship between intramuscular fat content and WBSF tenderness values ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our dataset, multiple proteins and phosphoproteins with functions in lipid metabolism were altered due to heat stress. At 14 DIM, perilipin (PLIN), a lipid droplet associated protein that participates in lipid droplet secretion from mammary epithelial cells 44 and acyl-CoA synthetase long chain family member 1 (ACSL), with a putative role in long chain fatty acid uptake by mammary cells 45 , were more abundant in HT cows. On the contrary, acetyl CoA carboxylase (ACACA), a rate limiting enzyme in milk fatty acid synthesis, was decreased in HT cows at 84 DIM.…”
Section: Discussionmentioning
confidence: 99%
“…Milk quality is affected by many factors, such as population genetic structure, reproductive performance, feeding and management, and is closely related to the main raw material composition of milk. Milk fat is an important component in butter and yogurt, and its content and composition are the main reference elements in milk quality evaluation ( Mu et al, 2021 ). Nowadays, milk fat content is not only one of the important indicators of core competitiveness of dairy industry, but also the main target feature of dairy cow breeding ( Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%